2000
DOI: 10.1038/35001072
|View full text |Cite
|
Sign up to set email alerts
|

The organizer factors Chordin and Noggin are required for mouse forebrain development

Abstract: In mice, there is evidence suggesting that the development of head and trunk structures is organized by distinctly separated cell populations. The head organizer is located in the anterior visceral endoderm (AVE) and the trunk organizer in the node and anterior primitive streak. In amphibians, Spemann's organizer, which is homologous to the node, partially overlaps with anterior endoderm cells expressing homologues of the AVE markers cerberus, Hex and Hesx1. For mice, this raises the question of whether the AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
333
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 496 publications
(363 citation statements)
references
References 30 publications
23
333
0
7
Order By: Relevance
“…During the development of many tissues, the action and local concentration of BMPs are controlled by specific antagonists and cell fates are specified by these molecules in a concentration-dependent manner (4,5,41). In vertebrate development, BMP4 is an important negative regulator of neural induction, whereas its antagonists Noggin and Chordin promote neural induction and are essential for patterning of the neural tube (5,16). As the BMP2/4 antagonists Chordin, Tsg, and Noggin are expressed in the thymus, it is possible that BMP2/4 signaling might work in a similar way to regulate T cell development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the development of many tissues, the action and local concentration of BMPs are controlled by specific antagonists and cell fates are specified by these molecules in a concentration-dependent manner (4,5,41). In vertebrate development, BMP4 is an important negative regulator of neural induction, whereas its antagonists Noggin and Chordin promote neural induction and are essential for patterning of the neural tube (5,16). As the BMP2/4 antagonists Chordin, Tsg, and Noggin are expressed in the thymus, it is possible that BMP2/4 signaling might work in a similar way to regulate T cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Noggin was first identified as a dorsalizing factor in the Spemann organizer of Xenopus embryos (12), and mouse Noggin is required for patterning of the neural tube (13) and cartilage morphogenesis (14). Chordin also functions as a dorsalizing factor of the Xenopus Spemann organizer (15), and as a regulator of mammalian brain development (16). Tsg, which in Drosophila embryos specifies dorsal cell fate, has recently been shown to function as an extracellular BMP antagonist in vertebrates (17)(18)(19).…”
mentioning
confidence: 99%
“…During organogenesis stages, Chordin is broadly expressed at very low levels (Scott et al, 2000; data not shown), with higher levels in the notochord and dorsal foregut endoderm (Bachiller et al, 2000;Stottmann et al, 2001). Besides the dorsal neural tube, Noggin is expressed in the notochord, dorsal foregut endoderm, and anterior neural ridge; in addition, Noggin appears to be expressed in some migrating cranial NCCs in mouse embryos Stottmann et al, 2001;Anderson et al, 2002).…”
Section: Bmp Antagonism Is Required For Survival Of Migratory Nccsmentioning
confidence: 91%
“…However, the severe chondrogenesis defects of Nog Ϫ/Ϫ mutants (Brunet et al, 1998) obscure phenotypes specific to the NCC-derived skeleton, and Chrd Ϫ/Ϫ ;Nog Ϫ/Ϫ mutants die before skeletogenesis (Bachiller et al, 2000). We, therefore, focused on craniofacial defects in Chrd Ϫ/Ϫ ; Nog ϩ/Ϫ mutants.…”
Section: Depletion Of Migratory Neural Crest Cells Inmentioning
confidence: 99%
“…6G′ and data not shown). Chordin (Chrd), encoding a BMP-antagonist specifically expressed in the APS and in one of its derivatives, the notochord (Bachiller et al, 2000), was absent in N1ICD epi embryos (n=4; Fig. 6I,I′).…”
Section: Notch Activation Impairs Axial Mesoderm Formation and Perturmentioning
confidence: 99%